2009
DOI: 10.1088/0963-0252/18/3/034014
|View full text |Cite
|
Sign up to set email alerts
|

Seeking sprite-induced signatures in remotely sensed middle atmosphere NO2: latitude and time variations

Abstract: Recent research on sprites shows these and other transient luminous events can exert a local impact on atmospheric chemistry, although with minor effects at global scales. In particular, both modelling and remote sensing work suggest perturbations to the background NO x up to a few tens of per cent can occur above active sprite-producing thunderstorms. In this study we present a detailed investigation of MIPAS/ENVISAT satellite measurements of middle atmospheric NO 2 in regions of high likelihood of sprite occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…MIPAS2D has been exploited to study the influence of transient luminous events on the atmosphere (Arnone et al, 2009b) and to analyze trends of ozone and several molecular species related to ozone chemistry: HNO 3 , N 2 O, NO 2 , N 2 O 5 , ClONO 2 , COF 2 , CFC-11 and CFC-12 by Papandrea et al (2010). Starting from January 2008 MIPAS duty cycle was increased back up to 100% and the mission has been extended to the end of 2013.…”
Section: Examples Of Resultsmentioning
confidence: 99%
“…MIPAS2D has been exploited to study the influence of transient luminous events on the atmosphere (Arnone et al, 2009b) and to analyze trends of ozone and several molecular species related to ozone chemistry: HNO 3 , N 2 O, NO 2 , N 2 O 5 , ClONO 2 , COF 2 , CFC-11 and CFC-12 by Papandrea et al (2010). Starting from January 2008 MIPAS duty cycle was increased back up to 100% and the mission has been extended to the end of 2013.…”
Section: Examples Of Resultsmentioning
confidence: 99%
“…At this magnitude, sprite‐NO x have detectable levels, especially under favorable conditions such as above intense sprite‐producing thunderstorms and with low background winds. This confirms what was suggested by the analysis of satellite observations of NO x by Arnone et al [], Rodger et al [], and Arnone et al [], with significant impact at local scale and negligible at global scale. On the other hand, we performed ad hoc calculations to resemble the method applied by Rodger et al []: We found that the use of partial columns of NO x extending down to 50 km altitude as they adopted is not sensitive enough to variations of sprite perturbations, since the lower atmospheric layers having the major weight in the partial columns have almost no response to sprite‐NO x .…”
Section: Discussionmentioning
confidence: 99%
“…Two independent observational studies investigated possible sprite‐induced chemical changes in middle atmosphere satellite measurements, using tropospheric lightning as a proxy of sprite activity. Arnone et al [] and their follow‐up work [ Arnone et al , ] found an anomalous NO 2 increase of 10% at 52 km altitude and of tens of percent at 60 km altitude in coincidence with active thunderstorms, possibly the result of sprite activity. Using a climatological approach, the multiyear study by Rodger et al [] found no global sprite‐signature in partial columns of NO x in the middle atmosphere concluding that sprites and other TLEs occurring below 70 km altitude cannot exert a significant global impact on neutral chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Arnone et al (2008) showed a statistical difference between the amount of NO 2 observed by the Michelson Interferometer for Passive Atmospheric Sounding mid-infrared emission spectrometer and thunderstorms activity within a field of view (FOV) of 500 × 30-km regions recorded by the Worldwide Lightning Location Network (WWLLN). Their statistical analysis and follow-up work (Arnone et al, 2009) indicates that NO 2 enhancements of about 10% at 52-km height and tens of percent at 60-km height immediately after thunderstorm activity. Rodger et al (2008) compared regional variations of column amounts of NO 2 observed by the Global Ozone Monitoring by Occultation of Stars UV-visible spectrometer with respect to the lightning activity obtained from Optical Transient Detector observations (Christian et al, 2003) in the tropical and northern midlatitude regions (Rodger et al, 2008).…”
Section: Citationmentioning
confidence: 99%